Halstead's Complexity Measure of a Merge Sort and Modified Merge Sort Algorithms - Balogun, Ghaniyyat Bolanle; Abdulraheem, Muhideen; Sadiku, Peter Ogirima; Taofeek, Olawale Debo; Adewale, Adebisi Sodiq (Jambura Journal of Informatics, 2023)
Complexity measuring tools in computer science are deployed to measure and compare different characteristics of algorithms to find the best one to solve a particular problem or that suits a specific situation. Also,  this is used to measure the complexity of a software program without running the program itself. Given this, Halstead's complexity metrics are deployed to compare the efficiency of two external sorting methods: the Merge Sort and the Modified Merge Sort Algorithms. The methodology used in achieving this lies in extracting operators and operands from the C_sharp (C#) implemented program of the two algorithms. Six Halstead metrics are evaluated using these operators and operands as parameters. The results show that the modified merge sort algorithm is much more efficient than the conventional Merge sort as it has a lower Program Volume, Program Difficulty, and Program Effort even though the advantage of a higher Intelligence content goes to the merge sort algorithm.